2016
DOI: 10.1007/s13361-015-1323-7
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Spatially Coded Apertures with a Miniature Mattauch-Herzog Mass Spectrograph

Abstract: In order to minimize losses in signal intensity often present in mass spectrometry miniaturization efforts, we recently applied the principles of spatially coded apertures to magnetic sector mass spectrometry, thereby achieving increases in signal intensity of greater than 10× with no loss in mass resolution Chen et al. (J. Am. Soc. Mass Spectrom. 26, 1633-1640, 2015), Russell et al. (J. Am. Soc. Mass Spectrom. 26, 248-256, 2015). In this work, we simulate theoretical compatibility and demonstrate preliminary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Over 10× increases in signal intensity were achieved, with no loss in mass resolution (Chen et al, 2015;Russell et al, 2015). Russell et al (2016) demonstrated that spatially coded apertures are compatible with a MHMS, hinting at possible applications to the IonCam system.…”
Section: Future Trends Technological Innovationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Over 10× increases in signal intensity were achieved, with no loss in mass resolution (Chen et al, 2015;Russell et al, 2015). Russell et al (2016) demonstrated that spatially coded apertures are compatible with a MHMS, hinting at possible applications to the IonCam system.…”
Section: Future Trends Technological Innovationsmentioning
confidence: 91%
“…Recent work from Russell et al (2016) focused on applying spatial coding techniques to magnetic sector MS in order to reduce the dichotomy between resolution and sensitivity inherent to MS. Although such techniques were proposed for use in MS in 1970 (Eckhardt and Gross, 1970), they have only recently been demonstrated (Chen et al, 2015;Russell et al, 2015).…”
Section: Future Trends Technological Innovationsmentioning
confidence: 99%
“…The measurement matrix then contains off-diagonal elements representative of multiplexing and there is no longer a single set of detector elements for each m/z. After determination of the measurement matrix H from the physics and architecture of the system, a mass spectrum can be reconstructed from the coded spectrum for an unknown compound or compounds by solving the inverse problem S ̂= H −1 g, where S ̂represents an estimate of the real spectrum S. 11 Previous work demonstrated the ability of aperture coding to increase the throughput without sacrificing resolution in a 90°m agnetic sector mass analyzer, 21,23 a Mattauch−Herzog mass analyzer, 22 and a cycloidal mass analyzer, 20 all of which were coupled with a position sensitive array detector. For the 90°a nd Mattauch−Herzog instruments, a distorted image of the aperture is projected on the detector that varies for each m/z due to the physics and architecture of the mass analyzer.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, miniaturization of mass spectrometers must contend with a trade-off between throughput and resolution that limits performance relative to traditional, full-scale laboratory instruments . Most commonly used miniature mass spectrometers are based on ion trap, quadrupole, or time-of-flight mass analyzers. Recently, there has been a renewed interest in miniature sector mass spectrometers due to the development of high-performance neodymium–iron–boron (Nd–Fe–B) permanent magnets that reduce the mass analyzer size and weight, and ion array detectors that offer simultaneous detection of ions over a wide mass range. Furthermore, the use of spatially coded apertures can break the trade-off between throughput and resolution in a sector mass spectrometer and increase throughput without sacrificing resolution. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation